Pengembalian Fungsi Baitul Mal Wa Tamwil melalui Strategi Penyelesaian Masalah Rentenir di Tasikmalaya - Nasrulloh, Agus Ahmad (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2020)
This study aims to find problems and solutions to restore the function of Baitul Mal Wa Tamwil through strategies to resolve moneylenders in Tasikmalaya. The method used is a qualitative-quantitative method with an analytic network process (ANP) approach. The results showed that the main problems that hampered the implementation of BMT functions caused by moneylenders in terms of educational problems were "weak education regarding usury (usury fiqh)", economic problems namely "urgent life necessities", environmental problems namely "very easy to access moneylenders" And from the regulatory problem namely "there is no firmness of the government towards moneylender". While the best solution to restore the function of BMT through the moneylender settlement strategy consists of an educational solution that is "socialization by academics and legislators regarding the importance of BMT, usury fiqh", economic solutions namely "convoluted non-interest government revolving fund assistance", the environmental solution is "the role of the RT and RW leaders to eradicate moneylenders", and a regulatory solution namely "the firmness of the government in overcoming the rampant moneylenders including sanctions".